2022
DOI: 10.3389/fmicb.2022.894637
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals Proteins Involved in the Mode of Action of β-Citronellol Identified From Citrus hystrix DC. Leaf Against Candida albicans

Abstract: Candida albicans is a fungus that lives primarily on the mucosal surfaces of healthy humans, such as the oral cavity, vagina, and gastrointestinal tract. This commensal organism can be controlled by other microbiota, while certain conditions can increase the risk of C. albicans outgrowth and cause disease. Prevalence of the drug-resistant phenotype, as well as the severity of C. albicans infection in immunocompromised patients, presents a challenge for scientists to develop novel, effective treatment, and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…An acyclic monoterpene, β ‐Citronellol, extensively studied and commonly observed in the EOs of plants such as rose, Pelargonium , and Citrus hystrix , displayed MIC and MFC values on C. albicans of 128 and 256 μg/mL, respectively. Moreover, their inhibitory effect on biofilms at 256 μg/mL was comparable to that of AMB treatment (Buakaew et al, 2022). Through proteomic analysis, Buakaew et al (2022) identified key proteomes with significant alterations, including cell wall proteins (Als2p and Rbt1p), oxidative stress response proteins (Sod1p and Gst2p), and ATP‐synthesis proteins (Atp3p and Cox1p).…”
Section: Antifungal Properties Of Natural Phytochemicalsmentioning
confidence: 90%
See 4 more Smart Citations
“…An acyclic monoterpene, β ‐Citronellol, extensively studied and commonly observed in the EOs of plants such as rose, Pelargonium , and Citrus hystrix , displayed MIC and MFC values on C. albicans of 128 and 256 μg/mL, respectively. Moreover, their inhibitory effect on biofilms at 256 μg/mL was comparable to that of AMB treatment (Buakaew et al, 2022). Through proteomic analysis, Buakaew et al (2022) identified key proteomes with significant alterations, including cell wall proteins (Als2p and Rbt1p), oxidative stress response proteins (Sod1p and Gst2p), and ATP‐synthesis proteins (Atp3p and Cox1p).…”
Section: Antifungal Properties Of Natural Phytochemicalsmentioning
confidence: 90%
“…Moreover, their inhibitory effect on biofilms at 256 μg/mL was comparable to that of AMB treatment (Buakaew et al, 2022). Through proteomic analysis, Buakaew et al (2022) identified key proteomes with significant alterations, including cell wall proteins (Als2p and Rbt1p), oxidative stress response proteins (Sod1p and Gst2p), and ATP‐synthesis proteins (Atp3p and Cox1p). Additionally, calmodulin (Cmd1p) expression increased with exposure to β ‐Citronellol, suggesting potential depletion of intracellular Ca 2+ , prompting yeast cells to activate the Ca 2+ compensation mechanism (Buakaew et al, 2022; Giuraniuc et al, 2023).…”
Section: Antifungal Properties Of Natural Phytochemicalsmentioning
confidence: 90%
See 3 more Smart Citations